IMPROVING READING SKILL BY USING SKETCH TO STRETCH STRATEGY IN OFFLINE LEARNING AND CONVENTIONAL IN ONLINE LEARNING TO LITERAL READING SUBJECT - Etty Pratiwi; Dewi Kartika Sari; Diana Luspa (Esteem Journal of English Education Study Programme, 2022)
This study aims to find out: (1) Is there a significant difference in the Sketch to Stretch strategy in improving students' reading skills in offline learning?, (2) Does conventionally have a significant difference in improving students' reading skills through online learning? and (3) Is there any contribution to increasing students' reading ability by increasing motivation to learn offline and online learning?. To determine the effectiveness of the Sketch to Stretch strategy, researchers had taken two research samples. The first group was taught using the Sketch to Stretch strategy in offline learning and the second used conventional strategies in online learning. To collect data, both groups were given a speech test and a learning motivation questionnaire. The results showed that there was a significant difference in learning motivation in the reading ability of students of the 1A semester English study program after being taught using the Sketch to Stretch strategy. So it can be concluded that the Sketch to Stretch strategy learning has an effect on reading ability and increasing student learning motivation.